Riset Pengembangan Pembelajaran Bahasa Indonesia Berbasis Nilai Kristiani di SMP Methodis 8 Medan - Enjelina Pitri Simamora; Natalia Debrianty Siringo-Ringo; Tride Mayora Hutasoit; Yesna Enika Lingga; Grace Angel Sirait; Irzi Armando Panjaitan; Debora Manihuruk (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore the integration of Christian values ​​in Indonesian language learning at Methodist 8 Medan Middle School. The main focus of this research is how Indonesian language teachers apply an integrative approach that not only educates academically but also shapes students' moral character through Christian values, such as love, patience and self-control. The research method used is qualitative, with interviews as the main data collection technique. The research results show that teachers use methods such as discussions and case studies to link religious teachings with language learning. Even though there are challenges, such as students' lack of interest in religious values ​​material, the implementation of Christian values ​​is still carried out through routine school activities such as monthly services and morning prayers, as well as collaboration between language teachers and religion teachers. This research provides an illustration that integrating Christian values ​​in learning can have a positive impact on student character, but requires a creative approach to attract student interest more effectively.